MEMAKNAI KATA â€˜WAJIBâ€™ DALAM PASAL 31 AYAT (1) UNDANG-UNDANG NOMOR 24 TAHUN 2009 TENTANG BENDERA, BAHASA, LAMBANG NEGARA, DAN LAGU KEBANGSAAN - Eko Rial Nugroho (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The issuance of Law Number 24 of 2009 concerning Flags, Language and State Symbols and the National Anthem, especially Article 31 paragraph (1) brings complications in international business transactions. Although the obligation to use the Indonesian language in a memorandum of understanding or agreement is to be welcomed, lawmakers do not think long and hard about the consequences of this provision for the business world, especially in international business transactions. The use of the phrase "mandatory" in Article 31 paragraph (1) raises its own problems, considering that there are no legal implications if the drafting of a memorandum of understanding or agreement involving Indonesian private institutions or individual Indonesian citizens does not use Indonesian. The formulation of the problem is how to interpret the word "mandatory" Article 31 paragraph (1) of Law Number 24 of 2009 Concerning Flags, Languages, National Emblems and National Anthems? The research method used is this research is normative legal research, namely research conducted based on library data as the main data which is secondary data and in the form of legal materials. Legal materials that have been grouped and classified are then analyzed using qualitative analysis. With this qualitative analysis, the steps taken are based on juridical logic, so that the problems can be explained in this research. The results of this study are that Article 31 paragraph (1) is a rule of law in which there is no sanction. The â€œmandatoryâ€ provisions contained in the norms of Article 31 paragraph (1) are interpreted as facultative provisions (can be) not imperative, because they do not include sanctions. In addition, the provisions of Article 31 paragraph (1) which include the word "mandatory" do not necessarily make agreements that do not use the Indonesian language null and void but are interpreted as having to use the Indonesian language without having the legal consequences of the agreement becoming null and void.